PERSPEKTIF Î±-AMILASE JAGUNG GERMINASI PADA KONVERSI PATI SAGU MENJADI MALTODEKSTRIN - , R.M. Bonodikun, Ir., Dr. Ir. Chusnul Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Î±-amylase (Î±-1-4 D-glucan glucanohydrolase EC 3.2.1.1) is enzymes that catalyze the hydrolysis of Î±-1,4-glycosidic linkages in the starch to form oligosaccharides and glucose. This enzyme is involved in the starch hydrolysis for the production of maltodextrin. A resource of Î±-amylase, which has not been much explored, is germinated corn germination Î±-amylase. On the other hand, a potential source of starch, which is needed to develop, is sago starch. Indonesia has 50 to 50.3% of the world's sagu plant. The potential of sago starch has not been explored very well. In this research, the potential of indigenous Î±-amylase from germinated corn for the conversion of sago starch (Metroxylon sago Rottb.) into maltodextrin was evaluated. The indirect experimental analysis was used to evaluate the perspective of germinated corn Î±-amylase in the conversion of sago starch into maltodextrins. The results show that (1) Perspective of sago starch in Indonesia: Indonesia is the habitat of sago palm that grows wild in the forest more than 6.7 million ha and produces 11,000 tons sago starch per-year